Work together… when apart challenges and what is need for effective virtual teams - Raval, R.R.; Ale Ebrahim, N.; Ahmed, S.; Taha, Z. (2010)
Increasingly competitive global markets and accelerating technological changes have increased the need for people to contact via electronic medium to have daily updates, the people those who could not able to meet face to face every day. Those who contact via electronic medium i.e. Virtual Team, are having number of benefit but to achieve these potential benefits, however, leaders need to overcome liabilities inherent in the lack of direct contact among team members and managers. Team members may not naturally know how to interact effectively across space and time. By this paper author try to throw some lights on the challenges that virtual team faces and try to elaborate what is needed for Virtual Team.